Peningkatan Pola Hidup Sehat melalui Pelatihan Teknik Menyikat Gigi pada Anak Usia Dini - Nurdiana Dewi; Beta Widya Oktiani; Sherli Diana; Hasnaa Ramadhani P.P.; Ainna Dewi Iriani (Universitas Lambung Mangkurat, 2023)
One of the dental and oral problems that often occurs is caries. Young children are at higher risk because their ability to maintain oral hygiene is still not optimal. Caries in children causes various impacts, including obstruct children's development, thereby reducing children's intelligence levels, which in the long term will have an impact on people's quality of life. Efforts to improve dental and oral health must begin as early as possible. One effort to improve dental and oral health is to instill in children the habit of maintaining healthy teeth through counseling and training. The counseling and toothbrushing training provided in this service activity is carried out to young children supported by parents and teachers. It is hoped that this outreach activity and toothbrushing training will provide an opportunity to teach children the importance of oral health and how to care for them properly. Counseling and training were carried out to students, teachers and parents at PAUDIT Nurul Fikri Banjarmasin using a participatory approach consisting of 3 stages, namely planning, implementation and evaluation. Counseling was carried out through animated videos, banners and dental puppets. Tooth brushing training was carried out with students brushing their teeth accompanied by parents and teachers. Based on the evaluation results, it was found that all parents were able to help their children brush their teeth better, and based on the results of interviews regarding the habit of brushing their teeth at home, all parents admitted that they always accompanied their children in brushing their teeth morning and night. It is hoped that this activity will become the basis for the establishment of the Little Dentist Program.